Estimated time to emergence of secondary intra-amniotic infection or inflammation since the onset of the preterm premature rupture of membranes - Satoko Tsuda; Takaaki Shinagawa; Keisuke Tsumura; Kunio So; Fumio Yamasaki; Atsushi Kawaguchi; Yukiko Nakura; Itaru Yanagihara; Makoto Nomiyama; Masatoshi Yokoyama (Elsevier, 2022)
Objective: Prematurity is the most important prognostic factor for infants born following preterm premature rupture of membranes (PPROM). Therefore, when PPROM occurs between 22 and 33 weeks of gestation, prolonging pregnancy is recommended. Determination of management strategies requires screening for the presence of intra-amniotic infection or inflammation at the time of PPROM diagnosis. If intra-amniotic infection/inflammation is not detected, it is important to monitor the patient to diagnose any new infection/inflammation. We examined the period from PPROM to secondary intra-amniotic infection/inflammation and associated factors. Materials and methods: This retrospective study was conducted at a single facility. We examined 26 patients who experienced PPROM between 26 and 33 weeks of gestation and were negative for intra-amniotic infection/inflammation at the time of diagnosis and underwent serial amniocentesis. Antibiotic therapy comprising ampicillin, amoxicillin, and clarithromycin for 7 days was started after the first amniocentesis. The period from PPROM to secondary intra-amniotic infection/inflammation was analyzed using a Kaplan-Meier survival curve. The onset of intra-amniotic infection/inflammation was considered as the time at which amniotic fluid bacterial culture results became positive, the time when amniotic fluid Interleukin (IL)-6 increased beyond 2.6 ng/mL, or the day of delivery if histological chorioamnionitis was observed in the delivered placenta. Patients were treated as censored if no intra-amniotic infection/inflammation could be confirmed in the amniotic fluid and delivered placenta. Results: The median time from PPROM to secondary intra-amniotic infection/inflammation was 18 days. Six patients developed intra-amniotic infection/inflammation, while 13 patients without intra-amniotic infections/inflammation delivered fewer than 7 days after PPROM. No confounding factors at the time of PPROM diagnosis were associated with the time from PPROM until secondary intra-amniotic infection/inflammation. Conclusions: The time between PPROM and onset of secondary intra-amniotic infection/inflammation appears prolonged. Treatments other than antimicrobial agents may need to be added to prolong pregnancy.